Prenatal Exposure to Low-Dose Diclofenac Sodium Does Not Affect Total Neuron Numbers in Spinal Segment T13 in Rats - Raǧbetli, M.Ç.; Kara, M.; Çölçimen, N.; Koyun, N.; Çakmak, G.; Akyol, V.; Deniz, Ö.G. (Elsevier B.V., 2018)
The main purpose of the present study was to investigate the effects of diclofenac sodium (DS) on the total number of neurons in segment T13 of the spinal cord of offspring of pregnant rats using stereological methods. Eighteen adult female Wistar albino rats weighing 150–200 g were used. Pregnant female rats were divided into three groups; a control group, a sham group and a DS (1 mg/kg, intramuscular) exposed group. The DS and sham groups received injection from the 5th day of gestation to the 19th. Twenty eight days after birth, the offspring rats were perfused with 4% buffered formalin. T13, which is one of transverse spinal cord segments, were isolated and processed for routine paraffin histology. 5 μm sections were obtained using a rotary microtome according to systematic random sampling strategies. Every 40th section was taken and sections were stained with modified Giemsa. All types of motor neuron cell were identified according to their morphology. In this study, the “disector-Cavalieri combination” method was used in the stereological examination of neurons. The motor neurons were counted in the right gray matter of the ventral horn in the spinal cord segment. The Kruskal–Wallis test was used for comparison the groups. In terms of motoneuron number, no significant difference among the groups was found (p > 0.05). In conclusion, our results indicated that prenatal exposure to DS has no effect on the total number of motor neuron of the offspring rats. © 2017 Elsevier B.V.
Keywords: Diclofenac Sodium; Motoneurons; Prenatal; Rat; Spinal Segment T13; Stereology